Factors affecting preventive behaviours of the complications of musculoskeletal disorders in industry workers: a qualitative study from Iran - Fazlollah Ahmadi; Sedigheh Sadat Tavafian; Zohre Moradi; Omran Ahmadi (BMJ Open)
Introduction Musculoskeletal disorders (MSDs) in the workplace are a major health problem which is significantly related to the adverse effects on the workforce’s health in different occupations, including the petrochemical industry employees. Many health behaviors can play a significant role in preventing complications caused by MSDs; however, in developing countries such as Iran, there is a lack of clarity about the factors affecting the prevention of complications from these disorders from the perspective of petrochemical industry employees. This study aimed to investigate effective factors to prevent complications caused by MSDs in petrochemical industry workers in Iran.Methods This qualitative study was conducted using the conventional content analysis method. The data were collected using in-depth and unstructured interviews with 23 employees and managers of the petrochemical industry. In this study, the participants were selected from different industry centres using the purposeful sampling method and based on the maximum diversity (work duties, age, level of education). The collected data were then analysed using the initial matrix developed based on the available literature.Results The analysis of the data from 23 interviews resulted in the identification of four main categories: educational-consultative support, organisational-management structure transformation, infrastructure security and physical environment redesign, and self-care necessity. These categories are the primary factors that influence the preventive behaviours related to MSDs among employees in the petrochemical industry.Conclusion The concepts that have emerged based on the results of this study can potentially help to develop comprehensive and appropriate training and health promotion programmes in creating, maintaining and promoting preventive behaviours of complications caused by MSDs in petrochemical industry workers.